Architectural organization and molecular profiling of 3D cancer heterospheroids and their application in drug testing - Nielsen, Boye Schnack; Madsen, Natasha Helleberg; Larsen, Jesper; Skandorff, Isabella; Gad, Monika; Holmstrøm, Kim (Frontiers in Oncology, 2024)
3D cancer cell cultures have enabled new opportunities for replacing compound testing in experimental animals. However, most solid tumors are composed of multiple cell types, including fibroblasts. In this study we developed multicellular tumor heterospheroids composed of cancer and fibroblasts cell lines. We developed heterospheroids by combining HT-29, MCF-7, PANC-1 or SW480 with 1BR.3.G fibroblasts, which we have previously reported support spheroid formation. We also tested fibroblast cell lines, MRC-5, GM00498 and HIF, but 1BR.3.G was found to best form heterospheroids with morphological similarity to in vivo tumor tissue. The architectural organization of heterospheroids was based on histological examination using immunohistochemistry. We found that HT-29 and MCF-7 cells developed spheroids with the cancer cells surrounding the fibroblasts, whereas PANC-1 cells interspersed with the fibroblasts and SW480 cells were surrounded by fibroblasts. The fibroblasts also expressed collagen-1 and FAP-α, and whole transcriptomic analysis (WTA) showed abundant ECM- and EMT-related expression in heterospheroids, thus reflecting a representative tumor-like microenvironment. The WTA showed that PANC-1 heterospheroids possess a strong EMT profile with abundant Vimentin and CDH2 expression. Drug testing was evaluated by measuring cytotoxicity of 5FU and cisplatin using cell viability and apoptosis assays. We found no major impact on the cytotoxicity when fibroblasts were added to the spheroids. We conclude that the cancer cell lines together with fibroblasts shape the architectural organization of heterospheroids to form tumor-like morphology, and we propose that the various 3D tumor structures can be used for drug testing directed against the cancer cells as well as the fibroblasts.